(untitled) (Global Journal of Management and Business Research, 2018)
While tax compliance has been an academic research topic in Ethiopia, there has not been detailed consideration of the major determinants of tax compliance in relation to taxpayers. The primary objective of this study was to identify the major determinants which affects the voluntary compliance behavior of tax payer’s in wolaita sodo town and Tercha Town in Dawuro zone. The study used an explanatory method of research design. Given the scaled ranking information of the dependent variable (tax compliance), a multiple linear regression model was applied to examine determinants of tax compliance in Wolaita Sodo and Tercha Town, Ethiopia. The study results from the survey conducted in study area using 290 respondents, indicate that tax compliance was influenced by the probability of being audited, financial constraints, and changes in government policy among thirteen potential determinants of tax non-compliance were examined in this study. The tax payers should always be treated equally, involve taxpayers (which are conclusive stakeholders in this tax system) on each of the tax issue and should work jointly, the tax authority needs to be strong enough as well as should be perceived as powerful by the taxpayers and voluntary compliance is enhanced when the tax authority administers the law fairly and the authority needs to strengthen itself by educating and training its employees both at home and abroad were few of the recommendations and implications forwarded to the tax authority in the study area in particular and the country in general based the findings and discussions.